Performance Enhancement of Spaceborne Cooler Passive Launch and On-Orbit Vibration Isolation System - Yeon-Hyeok Park; Mun-Shin Jo; Eung-Shik Lee; Hyun-Ung Oh (International Journal of Aerospace Engineering)
A spaceborne cryogenic cooler induces undesirable microvibration disturbances during its on-orbit operation, which is one of the main sources that degrades the image quality of submeter-level high-resolution observation satellites. Several types of vibration isolation systems based on passive approaches have been developed for reducing the microvibration of the cooler. A coil-spring-type passive vibration isolation system developed in a previous study has shown excellent performance in both launch vibration and on-orbit microvibration isolation. To improve the capability of the conventional cooler isolator, including the position sensitivity and launch vibration reduction, we propose a new version of a dual coil-spring-type passive vibration isolator system. The effectiveness of the newly proposed design was validated through a microjitter measurement test, position sensitivity test, and qualification-level launch vibration test of the isolator.